2011
DOI: 10.1103/physrevb.84.165303
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear transport phenomena in a two-subband system

Abstract: We study nonlinear transport phenomena in a high-mobility bilayer system with two closely spaced populated electronic subbands in a perpendicular magnetic field. For a moderate direct current excitation, we observe zero-differential-resistance states with a characteristic 1/B periodicity. We investigate, both experimentally and theoretically, the Hall-induced resistance oscillations which modulate the high-frequency magnetointersubband oscillations in our system if we increase the current. We also observe and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 39 publications
(96 reference statements)
5
28
0
Order By: Relevance
“…Therefore, the analysis of the HIRO amplitude using Eq. (1) can yield information on both sharp and smooth disorder components in a 2DES under study.In the regime of weak electric fields, the differential resistance acquires a negative quantum correction which scales with j 2 , as has been observed in GaAs heterostructures [3,4,6,8,[13][14][15][16][17][18][19]. In contrast to Eq.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Therefore, the analysis of the HIRO amplitude using Eq. (1) can yield information on both sharp and smooth disorder components in a 2DES under study.In the regime of weak electric fields, the differential resistance acquires a negative quantum correction which scales with j 2 , as has been observed in GaAs heterostructures [3,4,6,8,[13][14][15][16][17][18][19]. In contrast to Eq.…”
mentioning
confidence: 65%
“…In contrast, the second (inelastic) term in Eq. (3), given by τ in /τ ∼ E F /τ (k B T ) 2 (E F is the Fermi energy, τ in is the inelastic relaxation time), can be significantly larger than unity, especially in high density and low mobility 2DESs [8,[13][14][15][16][17][18][19]. In such systems, nonlinear transport at small j offers a convenient way to obtain τ in and thus access the strength of electron-electron interactions in the 2DES under study.…”
mentioning
confidence: 99%
“…At small magnetic fields we observed resistance oscillations with a period proportional to the magnetic field. We found that these oscillations are related to the current induced LandauZener transitions between Landau levels [12,17,19]. At higher magnetic fields another type of the resistance oscillations emerges with a period that is independent of the magnetic field.…”
Section: Introductionmentioning
confidence: 78%
“…As discussed numerous times [35][36][37][38][39][40][41][42][43][44][45][46], the observation of electron backscattering relies on the uniformity of the electric field within the bulk of the sample. Resonant mixing of MIRO and magneto-inter-subband resistance oscillations [47][48][49][50] further proves that MIRO is a bulk phenomenon. It is obvious that Refs.…”
Section: Eq (4)mentioning
confidence: 92%